Модели деструктивных субстантивов русского и итальянского языков - Rohava , Yuliya (Balcania et Slavia)
A significant part of the Russian and Italian vocabulary is represented by destructive nominations, the activity of which has grown due to the increase of destructive processes in the life of society. Modern journalism reflects a wide range of social relations: political, economic, cultural, sports, everyday life, etc. This article identifies groups of destructive nominations and demonstrates their realization in Russian and Italian publicism. The article also discusses forward “D (destructive lexical-semantic variant)” → “N (non-destructive lexical-semantic variant)” and inverse “N (non-destructive original lexical-semantic variant)” → “D (destructive derivative lexical-semantic variant)” models.